The Strategic Contribution of Community Empowerment Institutions in Formulating Participatory Inclusive and Responsive Development Policies - Akibu, Rifka S; Djafar, Franky (Journal of Social and Policy Issues, 2025)
Participatory, inclusive, and responsive development policies are essential principles in achieving democratic governance that reflects the actual needs of the community. However, efforts to implement such policies often face challenges at the local planning level. This study aims to analyze the strategic contribution of Community Empowerment Institutions (LPM) in the formulation of development policies through the mechanism of development planning deliberations in Molosifat U Village, Sipatana District, Gorontalo City. A descriptive qualitative approach was employed, using observation, interviews, and documentation as data collection techniques. The findings indicate that LPM plays a role as a facilitator, mediator, and motivator in encouraging community participation. Nevertheless, its contribution remains suboptimal due to low public involvement, limited evaluative capacity in assessing development proposals, and the influence of particular interests in the policy formulation process. On the other hand, advances in information technology serve as a supporting factor in enhancing participation and transparency. The study concludes that strengthening institutional capacity and increasing citizen engagement are crucial for enabling LPM to perform its strategic role more effectively in realizing participatory, inclusive, and responsive development policies.